Pengendalian Kualitas Statistik Air Higiene Sanitasi Menggunakan Peta Kendali SSRM - Salsabila Hasananda; Wibawati Wibawati (Inferensi, 2022)
Sanitary hygiene water is water that is used by everyone for bathing, washing, and toilet purposes where the quality standards for sanitary hygienic water are regulated in PERMENKES RI No. 32 of 2017. In the process of treating raw water into sanitary hygiene water, the water treatment plant unit pays attention to five quality characteristics, namely the pH level of the water, active chlorine concentration, turbidity, total hardness, and total solids. The quality control process carried out in the water treatment plant unit is classified as conventional by only checking the composition of each quality characteristic with the quality standard specifications without checking simultaneously. This study aims to determine statistical quality control through average monitoring of the sanitary hygiene water production process using a modern multivariate control chart resulting from the integration of the Multivariate Exponentially Weighted Moving Average (MEWMA) control chart with a spatial signed rank called the Spatial Signed Rank MEWMA (SSRM) control chart. The results showed that the characteristics of sanitary hygiene water had an influence on each other and did not have a multivariate normal distribution. So statistical quality control of sanitary hygiene water can be carried out using the SSRM control chart. This is because the SSRM control chart is good for data that is not normally distributed. This study also conducted monitoring of the average sanitary hygiene water process using the MEWMA control chart. The SSRM control chart is more suitable for controlling sanitary hygiene water than the MEWMA control chart because the number of out-of-control data observations on the SSRM control chart is greater than the MEWMA control chart.